Changes in net ecosystem exchange over Europe during the 2018 drought based on atmospheric observations. (26th October 2020) - Thompson, R. L.; Broquet, G.; Gerbig, C.; Koch, T.; Lang, M.; Monteil, G.; Munassar, S.; Nickless, A.; Scholze, M.; Ramonet, M.; Karstens, U.; van Schaik, E.; et al.
Abstract : The 2018 drought was one of the worst European droughts of the twenty-first century in terms of its severity, extent and duration. The effects of the drought could be seen in a reduction in harvest yields in parts of Europe, as well as an unprecedented browning of vegetation in summer. Here, we quantify the effect of the drought on net ecosystem exchange (NEE) using five independent regional atmospheric inversion frameworks. Using a network of atmospheric CO2 mole fraction observations, we estimate NEE with at least monthly and 0.5° × 0.5° resolution for 2009–2018. We find that the annual NEE in 2018 was likely more positive (less CO2 uptake) in the temperate region of Europe by 0.09 ± 0.06 Pg C yr −1 (mean ± s.d.) compared to the mean of the last 10 years of −0.08 ± 0.17 Pg C yr −1, making the region close to carbon neutral in 2018. Similarly, we find a positive annual NEE anomaly for the northern region of Europe of 0.02 ± 0.02 Pg C yr −1 compared the 10-year mean of −0.04 ± 0.05 Pg C yr −1 . In both regions, this was largely owing to a reduction in the summer CO2 uptake. The positive NEE anomalies coincided spatially and temporally with negative anomalies in soil water. These anomalies were exceptional for the 10-year period of our study. This article is part of the theme issue 'Impacts of the 2018 severe drought and heatwave in Europe: from site to continental scale'.